Relationship Between Husband's Support And The Incidence Of Anemia In Pregnancy In The Working Area of The Rumbai Health Center - Junaida Rahmi; Jasmi Jasmi; Asri Noviyanti; Yunetra Franciska (Poltekkes Kemenkes Palembang, 2022)
Anemia in pregnancy is currently still a major problem experienced by almost half of pregnant women in all countries in the world, including Indonesia. Anemia in pregnancy is a national problem because it reflects the value of socio-economic welfare of the community, and has a huge influence on the quality of human resources. The Maternal Mortality Rate (MMR) is an indicator of the success of health services. In 2014 the Maternal Mortality Rate (MMR) in the world was 289,000 soul. Several countries have quite high MMR, such as Africa with 179,000 people, South Asia with 69,000 people (WHO, 2014). The aim of the study was to determine the effect of husband's support on the incidence of anemia in pregnant women at the Rumbai Health Center in Pekanbaru City in 2017. The research method was analytic observational with a cross sectional approach. The research sample was 67 third trimester pregnant women in April - November 2017 using accidental sampling technique. The instrument used was a questionnaire. Data analysis used the chi square test. The results showed that 79.1% of the respondents were not at risk (20-35 years), 56.7% parity of respondents namely multiparas of 80.6% of respondents showed 56.7% of husbands providing support to pregnant women. And the results of the analysis showed that there was a relationship between husband's support and the incidence of anemia in pregnancy with a value (p = 0.032). From the research results it is hoped that the Puskesmas, especially health workers, can improve health education programs, especially regarding the importance of husband's support to prevent anemia in pregnant women.